Application of Contra Legem Principles in Judicial Rulings on Joint Property Characteristics - Fuad, Helmy Ziaul; Luth, Tohir; Hamidah, Siti; Sulistyarini, Rachmi (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2023)
This article examines the nuanced application of the contra legem principle by judicial panels in the adjudication of community property cases, particularly in the context of marital property. It highlights the evolving legal landscape and the importance of equitable distribution in contemporary law, underscoring the need to understand judicial reasoning in an era increasingly focused on fairness and gender equality. The study closely examines cases from religious courts, highlighting a trend in which judges have awarded a disproportionate share of community property to wives. This observation raises important questions about the balance between legal norms and the pursuit of equity in family law, and provides a critical lens through which to explore the dynamics of asset distribution and its broader implications in current legal frameworks. The research aims not only to outline judges' distribution formulas, but also to offer insights into why such decisions are increasingly relevant in today's legal discourse, marking a significant shift toward recognizing the complexities of marital property division. This study uses qualitative research methods with a legal descriptive analysis approach. A thorough legal source is case number 413/Pdt.G/2021/PA.Tng and a number of other legal materials related to the author's research topic. The results of the study show that the panel of judges applied the contra legem principle in deciding this matter based on sociological considerations and distributive justice.